2003
DOI: 10.1038/nature01521
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling angiosperm genome evolution by phylogenetic analysis of chromosomal duplication events

Abstract: Conservation of gene order in vertebrates is evident after hundreds of millions of years of divergence, but comparisons of the Arabidopsis thaliana sequence to partial gene orders of other angiosperms (flowering plants) sharing common ancestry approximately 170-235 million years ago yield conflicting results. This difference may be largely due to the propensity of angiosperms to undergo chromosomal duplication ('polyploidization') and subsequent gene loss ('diploidization'); these evolutionary mechanisms have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

52
1,358
5
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,439 publications
(1,417 citation statements)
references
References 28 publications
52
1,358
5
2
Order By: Relevance
“…The triplication of the At4-b BAC contig together with the comparative genetic mapping that revealed six copies of A. thaliana sequences in Brassica species (Lagercrantz and Lydiate 1996;Cavell et al 1998;Lagercrantz 1998;Parkin et al 2002Parkin et al , 2003 and less comprehensive previous FISH data (Jackson et al 2000; Ziolkowski and Sadowski 2002) suggest a hexaploid ancestor for the Brassiceae tribe. The presumed hexaploidization should not be confused with the genome duplications preceding the origin of Brassicaceae and evident in the A. thaliana genome (Bovers et al 2003) that are no longer detectable by cytogenetic means (Lysak et al 2001). Homeologous recombination in an allotetraploid, followed by imbalanced segregation of the products (Osborn 2004), should yield two instead of three labeled regions on pachytene chromosome complements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The triplication of the At4-b BAC contig together with the comparative genetic mapping that revealed six copies of A. thaliana sequences in Brassica species (Lagercrantz and Lydiate 1996;Cavell et al 1998;Lagercrantz 1998;Parkin et al 2002Parkin et al , 2003 and less comprehensive previous FISH data (Jackson et al 2000; Ziolkowski and Sadowski 2002) suggest a hexaploid ancestor for the Brassiceae tribe. The presumed hexaploidization should not be confused with the genome duplications preceding the origin of Brassicaceae and evident in the A. thaliana genome (Bovers et al 2003) that are no longer detectable by cytogenetic means (Lysak et al 2001). Homeologous recombination in an allotetraploid, followed by imbalanced segregation of the products (Osborn 2004), should yield two instead of three labeled regions on pachytene chromosome complements.…”
Section: Discussionmentioning
confidence: 99%
“…Although all studies revealed extensive duplications, some Arabidopsis segments were present either in less or more than three copies in Brassica (Truco et al 1996;Lan et al 2000;Babula et al 2003;Li et al 2003;Lukens et al 2003). However, at the level of short sequences, less than three copies might be caused by frequent loss in polyploids, and more than three copies might be caused by more remote genome duplications (Bovers et al 2003) or imbalanced homeologous recombination in allotetraploids (Osborn 2004). FISH mapping of a 431-kb Arabidopsis BAC contig to mitotic chromosomes and DNA fibers of B. rapa (Jackson et al 2000) and of two Arabidopsis BAC clones (150 kb) to B. oleracea (Ziolkowski and Sadowski 2002) supported an ancestral genome duplication for diploid Brassica species, although it did not clearly prove the genome triplication.…”
mentioning
confidence: 99%
“…We chose to compare the C-terminal domain of Arabidopsis thaliana with that of Brassica napus (Jack et al 1992;Pylatuik et al 2003). Recent studies in Brassicaceae dated the most recent common ancestor of Arabidopsis and Brassica between 20.4 and 14.5 million years ago (Bowers et al 2003;Schranz and Mitchell-Olds 2006). By comparing the C-termini of both species, we identified only one 3n-indel over an alignment of 189 nt.…”
Section: Codon Mutations In the C-terminal Domain Of Impdef1 And Impdmentioning
confidence: 99%
“…Individual grape chromosome segments resembling ancestral eudicot genome structure, or corresponding cacao chromosome segments, generally have five (infrequently six) best-matching G. raimondii regions and secondary matches resulting from pan-eudicot hexaploidy 7,8 (Fig. 2 and Supplementary Table 3.1).…”
mentioning
confidence: 99%